REAL EARNINGS MANAGEMENT: PERAN MEDIATOR INTERNAL CONTROL DALAM HUBUNGAN FINANCIAL DISTRESS DAN GOOD CORPORATE GOVERNANCE: REAL EARNINGS MANAGEMENT: THE MEDIATING ROLE OF INTERNAL CONTROL IN THE RELATIONSHIP BETWEEN FINANCIAL DISTRESS AND GOOD CORPORATE GOVERNANCE - Reskino, Reskino; Juliana, Anisa Nur; Basri, Yesi Mutia (Universitas Riau, 2025)
This study examines the direct and indirect relationship between real earnings management through internal control as a mediating variable. This study uses agency theory to explain the relationship between financial distress, good corporate governance, and real earnings management through internal control. Using quantitative methods, 126 secondary data sources in this study are listed on the Indonesia Stock Exchange (IDX). The SmartPLS application helps researchers analyze data using the partial least squares (PLS-SEM) method—the results of direct testing show that financial distress and good corporate governance affect internal control. Furthermore, financial distress and good corporate governance do not affect real earnings management, while internal control does. Then, the results of the indirect testing of this study are that internal control can mediate the relationship between financial distress and good corporate governance on real earnings management. This study complements the existing literature on real earnings management by focusing on empirical evidence of the relationship between financial distress, good corporate governance, and real earnings management. When studying the occurrence of real earnings management, the internal control component must be considered as a variable mediating the relationship between financial distress, good corporate governance, and real earnings management. This research can provide input for the Financial Services Authority (OJK) policy in formulating policies, regulations, and standards to minimize the opportunity for real earnings management in state-owned companies.